Factors Causing Language Anxiety of EFL Students in Classroom Presentation - Azwar Fadlan (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
AbstractThe purpose of this study is to identify : (1) Types of foreign language anxiety experienced by the students (2) factors causing language anxiety of EFL students. This research applied qualitative descriptive research method. It was carried out at Graduate Program of Makassar State University. The subject of this study were six students majoring in English who conducted a presentation seminar. They are all selected by using purposive sampling. The researcher observed and interviewed all G-class students conducting presentation seminar from February to April to identify type and factor of anxiety experienced by the students in a presentation seminar. The researcher made observations using video recording devices and field notes. Based on the result, there were three types of anxiety experienced by the students when doing presentation using English, namely anxiety related to positive (facilitative anxiety), anxiety related  to negative or destructive (debilitative anxiety) and anxiety which was not related to any of them. The researcher called it as non-effecting anxiety. As for some factors causing the students feel anxious in their speaking ability, generally they divided into two main factors, namely internal and external factors, but in the case of this study, the researcher found only internal factors.